Tipo de alimentación y grado de enterocolitis necrotizante en prematuros del Hospital Nacional Rebagliati, Lima 2015-2021: Type of feeding and degree of necrotizing enterocolitis in premature at the Hospital Nacional Rebagliati, Lima 2015-2021 - Falla Tamay, Gladys Marleny (2023)
Objetive: Evaluate the relationship between the type of feeding and the degree of NEC in premature infants at Edgardo Rebagliati Martins National Hospital, between 2015-2021. Methods: The study was observational, cross- sectional and retrospective. The clinical records of 81 patients were reviewed. The degree of NEC, the type of feeding (breast milk, formula and mixed), the volume at the beginning of the feeding and the volume of the food at the beginning of the NEC were extracted. Spearman's test was applied with a significance level of 0.05. Results: 39.5% of the patients received breast milk, grades I and III of NEC reached 37%. The feeding before day four was 77.8%. The volume of food obtained from the NEC (formula and mixed feeding), presented with the degree of NEC (Rho: 0.608 and 0.526 respectively: p<0.05), while the starting time for breast milk had a moderate impact with the degree of NEC (Rho: 0.431 and p<0.05). Conclusion: There  is a relationship between the volume of food (dairy and mixed formula) at the beginning of NEC with the degree of the disease. A relationship was also found between the day feeding (breast milk) was initiated with the degree of NEC in premature infants at the Edgardo Rebagliati Martins National Hospital, between the period 2015 to 2021.